Pengaruh Akuntabilitas dan Transparansi Pengelolaan Anggaran Terhadap Kinerja Keuangan pada Organisasi Perangkat Daerah (OPD) Provinsi Gorontalo - Andi Soraya Aprilia; Harun Blongkod; Lukman Pakaya (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to determine the effect of Accountability and Transparency of Budget Management on Financial Performance in Regional Apparatus Organizations (OPD) of Gorontalo Province. The method used in this study is a quantitative method with primary data obtained from questionnaire data whose measurements use an ordinal scale. The sample collection process uses purposive sampling or samples with certain criteria, namely based on criteria, namely OPD apparatus in the budget management sector with a total sample of 142 respondents and 29 OPDs in Gorontalo Province spread. The data analysis technique in this study uses Structural Equation Modeling (SEM) or Structural Equation Model operated through the AMOS 24 program. The results of the study indicate that accountability in budget management has no significant effect on OPD financial performance. Transparency in budget management has a positive and significant effect on financial performance. Simultaneously, accountability and transparency in budget management have a significant effect on OPD financial performance in Gorontalo Province explained by R-square 83.9%.